Wearables or infrastructure: contrasting approaches to collecting behavioural data in the home - Victoria, Shipp; Tim, Coughlan; Sarah, Martindale; Kher Hui, Ng; Elizabeth, Evans; Richard, Mortier; Stuart, Reeves (2014)
This paper examines and contrasts two approaches to collecting behavioural data within the home. The first of these involves filming from static video cameras combined with network logging to capture media consumption activities across multiple screens. The second utilises wearable cameras that passively collect still images to provide insights into food related behaviours. The paper compares the approaches from the perspective of the researchers and participants, and outlines the key benefits and challenges of each, with the aim of further mapping the space of possibilities now available when studying behaviour in the home.